NEURODIGITAL PROTOCOLS AND PARAMETERS FOR ASSESSING MOTOR SKILLS IN ELDERLY PEOPLE: AN INTEGRATIVE LITERATURE REVIEW - Cavalheiro, Geovani Rafaele Lima; Berlese, Denise Bolzan; dos Santos, Geraldine Alves; Sidekum, Djuli Margô Naissinger (Seven Editora, 2025)
This study aims to investigate neurological protocols used to assess motor skills in older adults, with special emphasis on active digital games or exergames. The integrative literature review was conducted based on automated searches using descriptors by area of interest. The time frames were searched between January 1, 2022, and August 29, 2024, on the Scopus, PubMed, Scielo, and Periódicos Capes platforms, chosen for their relevance in the areas of motor development and control. The search strings were: (“Elderly”) AND (“motor skill”) AND (“exergames”) OR (exergaming) AND (“assessment”). Initially, 109 articles were found by title. After applying the inclusion and exclusion criteria, 31 articles remained, of which 20 had full text available. Next, the titles, abstracts, and full texts were analyzed. During this process, one repeated study, one incomplete study, and one study related to children were excluded, thus 17 articles were selected for final analysis. As a result, exergames show great potential to stimulate and improve health in the elderly, with proven efficacy in most of the studies analyzed. However, their use as an assessment tool has not been explored, highlighting a gap in the literature. There is a need for research that investigates their application for more accurate assessments and comparisons with traditional methods. Exploring this potential can optimize the use of exergames and expand their benefits for this population. DOI: https://doi.org/10.56238/sevened2024.037-179